2012
DOI: 10.1017/s0956792512000381
|View full text |Cite
|
Sign up to set email alerts
|

Waveless subcritical flow past symmetric bottom topography

Abstract: The subcritical flow of a stream over a bottom obstruction or depression is considered with particular interest in obtaining solutions with no downstream waves. In the linearised problem this can always be achieved by superposition of multiple obstructions, but it is not clear whether this is possible in a full nonlinear problem. Solutions computed here indicate that there is an effective nonlinear superposition principle at work as no special shape modifications were required to obtain wave-cancelling solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 22 publications
2
21
1
Order By: Relevance
“…This paper follows the work of Forbes [8] and Hocking et al [11], who found solutions to the nonlinear problem of subcritical flow over a semi-elliptical obstruction on the stream bed with no downstream waves, and Holmes et al [12], who found waveless nonlinear solutions for subcritical flow over two Gaussian obstructions. Forbes [8] calculated the ellipse height and length values that would produce waveless solutions at a Froude number of F = 0.5, with these results presented as contours in parameter space.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…This paper follows the work of Forbes [8] and Hocking et al [11], who found solutions to the nonlinear problem of subcritical flow over a semi-elliptical obstruction on the stream bed with no downstream waves, and Holmes et al [12], who found waveless nonlinear solutions for subcritical flow over two Gaussian obstructions. Forbes [8] calculated the ellipse height and length values that would produce waveless solutions at a Froude number of F = 0.5, with these results presented as contours in parameter space.…”
Section: Introductionmentioning
confidence: 77%
“…Cases involving obstructions of both positive and negative heights will be examined. In an earlier paper [12], the authors considered the fully nonlinear problem, and contours in parameter space representing waveless solutions were found. Here, the problem is revisited using a weakly nonlinear analysis in the form of the Korteweg-de Vries (KdV) equation, and comparisons are made with the results of the fully nonlinear problem.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The converse statements of this corollary are not true because the waveless solutions with δ = 0, Fr = Fr d exist both for Fr < 1 (see Forbes 1982;Maklakov 1995;Holmes et al 2013) and Fr > 1 (see Forbes & Schwartz 1982;Vanden-Broek 1987). But the solutions with δ = 0, Fr < 1 exist only if the parameters of the disturbance are chosen by a special way.…”
Section: Signs Of the Wave Resistance And Upstream Flow Parametersmentioning
confidence: 98%